2018
DOI: 10.1016/j.bcp.2018.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol targets nucleoredoxin/dishevelled interactions and stimulates phosphatidylinositol 4-phosphate production in vivo and in vitro

Abstract: Nucleoredoxin (NXN) is a redox-regulating protein potentially targeted by reactive oxygen species (ROS). It regulates molecular pathways that participate in several key cellular processes. However, the role of NXN in the alcohol liver disease (ALD) redox regulation has not been fully understood. Here, we investigated the effects of ethanol and ethanol plus lipopolysaccharide, a two-hit liver injury model (Ethanol/LPS), on NXN/dishevelled (DVL) interaction and on DVL-dependent phosphoinositides production both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 53 publications
1
19
0
Order By: Relevance
“…This is a widely used model that includes the high‐fat Lieber‐DeCarli diet regime plus single‐binge of ethanol to induce the early stage of ALD 22 . The experimental procedure was performed as previously reported 12 . Briefly, 5% ethanol in liquid diet was administered for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a widely used model that includes the high‐fat Lieber‐DeCarli diet regime plus single‐binge of ethanol to induce the early stage of ALD 22 . The experimental procedure was performed as previously reported 12 . Briefly, 5% ethanol in liquid diet was administered for 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that NXN negatively regulates WNT/β‐catenin pathway by interacting with dishevelled (DVL), an essential mediator in the Wnt signalling; interestingly, NXN/DVL interaction is dissociated by increased ROS production which enables DVL to activate the downstream WNT/β‐catenin signalling pathway 6 . Recently, we have shown that NXN/DVL interaction ratio is altered by ethanol and as a result, this alteration disrupts DVL‐dependent processes during ALD progression 11,12 . These evidences have suggested that other signalling pathways regulated by NXN might be also altered in ALD.…”
Section: Introductionmentioning
confidence: 98%
“…Lipopolysaccharide and EtOH concentrations were chosen from a report by Arellanes‐Robledo et al (2018) that demonstrated that LPS at 1 µg/mL and EtOH at 100 mmol/L in these cells produced a suitable response to investigate compounds with putative immunomodulatory activity such as SVT …”
Section: Methodsmentioning
confidence: 99%
“…A no template control, a target reagent sample and a negative sample were included on the plate. GAPDH (gene ID: 24383) (Rn01775763_g1) was used as the internal control, and the relative gene expression was calculated using the Livak method, as follows:2-ΔCtCtexperimental target gene-Ctexperimental housekeeping gene-Ctcontrol target gene-Ctcontrol housekeeping gene…”
Section: Methodsmentioning
confidence: 99%
“…Among the various contributors of the liver injury, accumulation of lipids in cytoplasm of hepatocytes takes centre stage, with not only the quantity but the quality of lipids determining severity of the damage . For example, sphingolipids (SLs) components such as acid sphingomyelinase (ASM) or ceramide (Cer) act as secondary contributors to alcoholic (ASH) or non‐alcoholic steatohepatitis (NASH).…”
Section: Introductionmentioning
confidence: 99%